Purtscher-Like Retinopathy - Rita Massa; Carolina Vale; Mafalda Macedo; Maria João Furtado; Miguel Gomes; Miguel Lume; Angelina Meireles (Case Reports in Ophthalmological Medicine)
Purtscher-like retinopathy is associated with retinal hemorrhages and ischaemia probably due to the complement-mediated leukoembolization. It is a rare and severe angiopathy found in conditions such as acute pancreatitis. Case. We present a case of a 53-year-old man who presented with a Purtscher-like retinopathy associated with the development of acute pancreatitis in the context of a Klatskin tumour (a hilar cholangiocarcinoma). The ophthalmologic evaluation revealed the best corrected visual acuity (BCVA) of 20/32 in the right eye (RE) and of 20/40 in the left eye (LE); biomicroscopy of anterior segment showed scleral icterus and fundoscopy revealed peripapillary cotton-wool spots, optic disc edema, and RPE hypo- and hyperpigmentation in the middle peripheral retina in both eyes with an intraretinal hemorrhage in the LE. 15 months after the initial presentation, without ophthalmological treatment, there was an improvement of BCVA to 20/20 in both eyes and optical coherence tomography (OCT) revealed areas of reduction of retinal nerve fiber layer thickness corresponding to the previous cotton-wool spots. Conclusion. Purtscher-like retinopathy should not be neglected in complex clinical contexts. Its unclear pathophysiology determines an uncertain treatment strategy, but a meticulous follow-up is compulsory in order to avoid its severe complications.